Occupational risk factors for nasopharyngeal cancer among female textile workers in Shanghai, China. Issue 1 (16th December 2005) - Li, W; Ray, R M; Gao, D L; Fitzgibbons, E D; Seixas, N S; Camp, J E; Wernli, K J; Astrakianakis, G; Feng, Z; Thomas, D B; Checkoway, H
Abstract : Aims: To investigate whether occupational exposure to dusts and chemicals in the Chinese textile industry are associated with risk of nasopharyngeal cancer. Methods: Sixty seven nasopharyngeal carcinoma (NPC) cases identified during 1989–98 and a random sample (n = 3188) of women were included in a case cohort study nested in a cohort of 267 400 women textile workers in Shanghai, China. A complete occupational history of work in the textile industry was obtained for each woman. A job exposure matrix developed by experienced industrial hygienists was used to assess exposures to specific dusts and chemicals. Results: Risk of NPC is associated with cumulative exposure to cotton dust. The hazard ratio for women cumulatively exposed to >143.4 mg/m 3 × years of cotton dust was 3.6 (95% CI 1.8 to 7.2) compared with unexposed women. Trends of increasing risk were also found with increasing duration of exposure to acids and caustics (p = 0.05), and with years worked in dyeing processes (p = 0.06). Women who worked at least 10 years in dyeing processes had a 3.6-fold excess risk of NPC (95% CI 1.0 to 12.1). Conclusions: Occupational exposure to cotton dust, acids, and caustics, and work in dyeing and printing jobs in the textile industry may have increased risk of NPC in this cohort.